ANALYSIS OF THE WEAKENING STATUS OF THE INDONESIAN PASSPORT FROM AN INTERNATIONAL PERSPECTIVE AND ITS IMPACT ON INDONESIAN CITIZENS - Rizki Rivaldi Hidayat; M. Naufal Arafi; Rizky Hidayat (Jurnal Ikhtibar Nusantara, 2026)
A passport is a crucial instrument in international relations that reflects a country’s standing in the eyes of the world. In recent years, the ranking of the Indonesian passport has declined in various global passport indices, such as the Henley Passport Index and the Passport Index. This decline has impacted the mobility of Indonesian citizens (WNI), particularly in terms of international travel, education, business, and migrant labour. This study aims to analyse the factors contributing to the weakening of the Indonesian passport’s standing from an international perspective, as well as its impact on Indonesian citizens. The research method employed is a qualitative approach with a descriptive focus, utilising a literature review of various academic sources, international reports, and global immigration policy data. The findings indicate that document security, issues of illegal migration, international diplomacy, economic and political stability, and the visa policies of other countries are the primary causes of the weakening of the Indonesian passport’s standing. The impacts include increased travel restrictions, higher visa processing fees, and a decline in the global competitiveness of Indonesian citizens. Therefore, strengthening international diplomacy, improving the quality of the immigration system, and enhancing Indonesia’s global image are necessary to reinforce the standing of the Indonesian passport.